PROBABILITY ANALYSIS OF COST AND TIME ACCURACY USING THE CONCEPT OF YIELD VALUE AND MONTE CARLO (Case Study: SIBS Girls' Dormitory Building Construction Project) - Putri Ayu Mentari; Mirnayani . (Fakultas Teknik, Universitas Wiraraja, 2026)
The SIBS Women's Dormitory Building Construction Project faced significant delays and design alterations, causing changes in project costs and timelines. This study aims to identify delay factors, evaluate cost and time performance using the Earned Value Method (EVM), and estimate the probability accuracy of cost and duration using Monte Carlo simulation. Data were collected through direct observations, stakeholder interviews, and document analysis. Main factors causing delays include adverse weather, challenging site accessibility, delayed material deliveries, and a design change from three to four floors. Initial completion estimates of 623 days showed an accuracy probability of 2.03%, while the revised EVM estimate of 652 days significantly improved accuracy to 73.91%. The probability accuracy for remaining costs of Rp1.948.950.796 using EVM was 19.61%. The findings suggest combining EVM with Monte Carlo simulation effectively enhances predictions and management of construction project costs and durations.